Current Status of Adoption of No-till Farming in the World and Some of its Main Benefits - Derpsch, Rolf; Friedrich, Theodor; Kassam, Amir; Li, Hongwen (International Journal of Agricultural and Biological Engineering, 2010)
In 1999 no-tillage farming, synonymous of zero tillage farming or conservation agriculture, was adopted on about 45 million ha world wide, growing to 72 million ha in 2003 and to 111 million ha in 2009, corresponding to an growth rate of 6 million ha per annum. Fastest adoption rates have been experienced in South America where some countries are using no-tillage farming on about 70% of the total cultivated area. Opposite to countries like the USA where often fields under no-tillage farming are tilled every now and then, more than two thirds of the area under no-tillage systems in South America is permanently not tilled; in other words once adopted, the soil is never tilled again. The spread of no-tillage systems on more than 110 million ha world-wide shows the great adaptability of the systems to all kinds of climates, soils and cropping conditions. No-tillage is now being practiced from the artic circle over the tropics to about 50º latitude south, from sea level to 3,000 m altitude, from extremely rainy areas with 2,500 mm a year to extremely dry conditions with 250 mm a year. No-till farming offers a way of optimizing productivity and ecosystem services, offering a wide range of economic, environmental and social benefits to the producer and to the society. At the same time, no-till farming is enabling agriculture to respond to some of the global challenges associated with climate change, land and environmental degradation, and increasing cost of food, energy and production inputs. The wide recognition of no-till farming as a truly sustainable system should ensure the spread of the no-till technology and the associated practices of organic soil cover and crop rotation, as soon as the barriers to its adoption have been overcome, to areas where adoption is currently still low. The widespread adoption globally also shows that no-tillage farming cannot any more be considered a temporary fashion or a craze; instead largely through farmers’ own effort, the system has established itself as a farming practice and a different way of thinking about sustainable agro-ecosystem management that can no longer be ignored by scientists, academics, extension workers, farmers at large as well as equipment and machine manufacturers and politicians. Keywords: world-wide no-till adoption, zero tillage adoption, conservation agriculture, soil health, climate change, ecosystem services DOI: 10.3965/j.issn.1934-6344.2010.01.0-0 Citation: Rolf Derpsch, Theodor Friedrich, Amir Kassam, Li Hongwen. Current status of adoption of no-till farming in the world and some of its main benefits. Int J Agric & Biol Eng, 2010; 3(1): <span style="line-height: 140%; font-family: